Quantitative reproducibility of mass spectra in matrix‐assisted laser desorption ionization and unraveling of the mechanism for gas‐phase peptide ion formation. (27th February 2013) - Ahn, Sung Hee; Park, Kyung Man; Bae, Yong Jin; Kim, Myung Soo
Abstract : In a previous study on matrix‐assisted laser desorption ionization (MALDI) of peptides using α ‐cyano‐4‐hydroxycinnamic acid (CHCA) as a matrix, we found that the patterns of single‐shot spectra obtained under different experimental conditions became similar upon temperature selection. In this paper, we report that absolute ion abundances are also similar in temperature‐selected MALDI spectra, even when laser fluence is varied. The result that has been obtained using CHCA and 2, 5‐dihydroxybenzoic acid as matrices is in disagreement with the hypothesis of laser‐induced ionization of matrix as the mechanism for primary ion formation in MALDI. We also report that the total number of ions in such a spectrum is unaffected by the identity, concentration and number of analytes, i.e. it is the same as that in the spectrum of pure matrix. We propose that the generation of gas‐phase ions in MALDI can be explained in terms of two thermal reactions, i.e. the autoprotolysis of matrix molecules and the matrix‐to‐analyte proton transfer, both of which are in quasi‐equilibrium in the early matrix plume. Copyright © 2013 John Wiley & Sons, Ltd.